By Induction. Remember: prove a base case assume true for n=k k>base case prove for n=k+1 Prove for n=1 1 = 1(2)/2 Assume true for n=k k>1 Σki=1i = k(k+1)/2 Prove true for n=k+1; Show: Σk+1i=1i = (k+1)(k+2)/2 since Σki=1i = k(k+1)/2 then Σki=1i+k+1 = k(k+1)/2 + k+1 Σki=1i + k+1 = Σk+1i=1i Σk+1i=1i = [k(k+1) + 2(k+1) ]/2 = (k2+k+2k+2)/2 = (k2+3k+2)/2 = (k+1)(k+2)/2
Prove the for any Fibonacci number Fk, Fk < (5/3)i (remember 1, i = 1 Fi = 1, i = 2 Fi-1+Fi-2, i > 2 Base Case: i = 1; 1 < (5/3)1 Assume true for all values 1≥j≥k Prove true for k+1 Fk+1 = Fk + Fk-1 Fk + Fk-1 < (5/3)k + (5/3)k-1 < (3/5)(5/3) (5/3)k + (3/5)2(5/3)2(5/3)k-1 = (3/5)(5/3)k+1+(3/5)2(5/3)k+1 = (5/3)k+1(3/5 + 9/25) = (5/3)k+1(15+9)/25 = (5/3)k+1(24)/25 < (5/3)k+1